Peningkatan Produktivitas Ayam dengan Formulasi Ransum Padat Nutrisi Berbahan Baku DDGS di Lahan Pantai - Sudarisman Sudarisman; Yunianta Yunianta; Citravia Agustin (Politeknik Negeri Jember, 2022)
One of the obstacles to the use of coastal land for the cultivation of laying hens is the high ambient temperature with extreme fluctuations in heat and cold, causing low feed consumption and productivity. The purpose of this study was to compile a nutrient-dense ration formulation with raw materials for distiller dried grains with soluble (DDGS) with feed in the form of crumble. This study was conducted in coastal areas using DDGS 10% (P1), DDGS 30% (P2) and DDGS 30% and methionine 1% (P3) using 180 laying hens of the Lohman Brown’s strain aged 18 months with 3 treatments and 3 tests. The results showed that the hen day average (HDA) and feed conversion showed a very noticeable difference (P<.01) successively, namely 78.62%; 85,07%; and 89.53% and 2.45%; 2,33%; and 2.00%. laying hens and can increase egg production in coastal land if methionine is added.